2018
DOI: 10.1167/18.4.19
|View full text |Cite
|
Sign up to set email alerts
|

No special treatment of independent object motion for heading perception

Abstract: How do we judge the direction of self-motion (i.e., heading) in the presence of independent object motion? Previous studies that examined this question confounded the effects of a moving object's speed and its position on heading judgments, and did not examine whether the visual system uses salient nonmotion visual cues (such as color contrast and binocular disparity) to segment a moving object from global optic flow prior to heading estimation. The current study addressed these issues with both behavioral tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
38
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(48 citation statements)
references
References 52 publications
(117 reference statements)
7
38
1
Order By: Relevance
“…Previous studies found that independently moving objects affected heading judgments only when they obscured or were in close proximity to the FOE of the background optic flow (Layton & Fajen, 2015, 2016a, 2016bRoyden & Hildreth, 1996;Warren & Saunders, 1995). In contrast, Li et al (2018) showed that independently moving objects can affect heading judgments even when they are not close to the FOE of the background optic flow. In Experiment 2, we sought to test whether normal PLWs and scrambled PLWs could bias heading estimation in a similar way when they are away from the FOE of the background optic flow.…”
Section: Experiments 2: Heading Biases When Walkers Are Away From the Foementioning
confidence: 93%
See 4 more Smart Citations
“…Previous studies found that independently moving objects affected heading judgments only when they obscured or were in close proximity to the FOE of the background optic flow (Layton & Fajen, 2015, 2016a, 2016bRoyden & Hildreth, 1996;Warren & Saunders, 1995). In contrast, Li et al (2018) showed that independently moving objects can affect heading judgments even when they are not close to the FOE of the background optic flow. In Experiment 2, we sought to test whether normal PLWs and scrambled PLWs could bias heading estimation in a similar way when they are away from the FOE of the background optic flow.…”
Section: Experiments 2: Heading Biases When Walkers Are Away From the Foementioning
confidence: 93%
“…A blank area in the size of the walker and void of background dots was placed behind the walker, such that none of the background points interspersed the walker at any time during the trial. This was done in order to make the current experiment more comparable to similar experiments, by Li et al (2018). As in Experiment 1, a control condition with no moving object was also tested.…”
Section: Visual Displaymentioning
confidence: 99%
See 3 more Smart Citations